Effects of operating parameters on dielectric barrier discharge non-thermal plasma ozone generator performance and NO Conversion - Chonpan Phurin; Theinnoi Kampanart; Iamcheerangkoon Teerapong; Promhuad Punya; Sittichompoo Sak (E3S Web of Conferences)
This research investigates how gas flow rate, oxygen concentration, discharge voltage, and frequency influence the production of ozone (O3) and nitrogen dioxide (NO2). Findings reveal that increased discharge voltage and frequency enhance O3 and NO2 formation by raising free charge and energy, facilitating oxygen molecule dissociation and three-body collisions. Lower gas flow rates lead to higher specific energy density (SED) and thus greater O3 and NO2 concentrations due to longer oxygen molecule residence times. Higher oxygen concentrations in the feed gas result in a linear increase in O3 and NO2 levels, driven by more oxygen molecules available for ozone production which enhances NO oxidation. Additionally, increased input ozone concentration improves NO oxidation to NO2 and further increasing O3 input resulted in NO2 reduction via N2O5 formation. However, the presence of N2O5 was not quantified due to limitation in measurement. Understanding these factors is crucial for optimizing ozone generation for controlling NO2 emissions, with important implications for air purification and pollutant control.